Establishment of Mosque-Based Baitut-Tamwil in Nagasaribu Village, North Padang Lawas Regency to Support Productive Economic Communities - Hardana, Ali; Efendi Siregar, Sulaiman; Wahyu Utami, Try; Hasibuan, Lismawati (Help: Journal of Community Service, 2024)
People in Nagasaribu Village, North Padang Lawas District, produce traditional food and market snacks in their homes. These home industries are mainly managed by mothers (wives) to earn extra money to support their families. The community of Nagasaribu Village will definitely experience difficulties if they need additional funds for small amounts of capital because they are small producers. The focus of this community assistance was to establish a mosque-based Baitut-Tamwil savings and loan cooperative. They also conducted organizational (managerial) training as well as training on how to utilize the cooperative to provide savings and loan services based on sharia economic principles. One form of community empowerment is community service activities, which aim to foster creativity by encouraging, motivating, and increasing awareness of the potential of the community. Skills development and community economic development can be achieved through mentoring that is tailored to the needs and potential of the community. The high level of participation of participants and the achievement of activity targets are indicators of the success of this community service activity. However, one challenge that may continue to occur is the reluctance of community members participating in the mentoring program to start the business that has been taught in this activity.